Service Marketing Mix Affects to Decision Buying Engine Oil Lubricants of Consumers in Mueang District, Phitsanulok Province - Inkhot, Phattaranan; Yawila, Lasda; Sittioum, Rattana (Journal for Developing the Social and Community, 2021)
The purposes of research were 1) to study compare the purchasing decisions of engine oil lubricants of consumers in Mueang District, Phitsanulok Province Classified by personal factors. 2) to study service marketing mix factors affects the decision to buy engine lubricants of consumers in Mueang District, Phitsanulok Province. Questionnaires were used to collect data of 385 staff by stratified simple random sampling technique, Then Frequency, means, percentage, standard deviation, t-test, One-Way ANOVA (F-Test) and multiple linear regression were applied of data analysis. The research found that 1) Consumers in Mueang District, Phitsanulok with personal factors such as age, educational, and occupation is different. There are opinions regarding the decision on Buying Engine Oil lubricant in statistically significant difference at 0.05 2) Marketing promotion factors, process factors and Product factors also has an important affection the decision Buying Engine Oil lubricant in Mueang District, Phitsanulok Province with statistical significance of 0.05